ANALISIS PENGARUH FAKTOR INTERNAL BANK TERHADAP PENYALURAN KREDIT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2011 (Students' Journal of Accounting and Banking, 2013)
The purpose of this study is to find empirical evidence and analyze the effect of Capital Adequacy Ratio, Return on Assets, Loan to Deposit Ratio, Loan and the amount of non-perfoming loans extended to banking companies in Indonesia Stock Exchange. The sample used in this study were 25 companies using purposive sampling technique, sampling technique is based on the criteria, which is a company listed on the Stock Exchange and the companies that submit financial statements for 2009-2011. Statistical tools used in this study using a multiple linear regression model. From the results of tests performed on the results of this study showed that the variable CAR negative and significant effect on lending. Whereas the ROA variable positive and significant effect on lending. For LDR variable is not significant positive effect on lending while the NPL and no significant negative effect on lending.Keywords: CAR, ROA, LDR, NPL